Elevation changes of the Greenland ice sheet derived from multi-temporal TanDEM-X DEM data from 2010 to 2015 - Wessel, Birgit; Leichtle, Tobias; Wohlfart, Christian; Abdullahi, Sahra; Kerkhoff, Silke; Roth, Achim (2017)
In this presentation we analyze three digital elevation models (DEM) of Greenland produced with data recorded by the TanDEM-X (TerraSAR add-on for digital elevation measurement) mission. During the TanDEM-X mission several area-wide coverages of Greenland were acquired. From this data we produce three DEMs with distinct temporal coverage: one capturing the winter 2010/11, one containing the winter 2011/12 and one from the winter 2015/16. These DEMs possess a spatial resolution of 0.4 arc seconds (i.e. corresponding to 12 m) and are composed of around 3000 individual interferometric synthetic aperture radar (InSAR) DEM scenes each. X-Band SAR penetrates the snow and ice pack by several meters depending on the snow structures, the acquisition parameters, and the di-electric constant of the medium. Hence, the resulting SAR measurements do not represent the real surface but the elevation of the mean phase center of the backscattered signal. As a first step, all DEMs are vertically calibrated to achieve comparable heights. For the conducted iterative least-squares block adjustment, ICESat (Ice, Cloud, and land Elevation Satellite) elevation measurements are used as ground control points (GCPs) on the outer coastal regions where rock and surface scattering predominates (REF). For the inland of Greenland, tie-point chips within the overlapping areas of the individual scenes are employed for block adjustment. In a second step, the spatio-temporal characteristics are analyzed in detail. We found that the inner main body of Greenland seems to be relatively stable within the observed time frame from 2010 to 2015. In contrast, several significant height change events (negative as well as positive) occur at the outlet glaciers. Based on this high-resolution DEM data set we can also monitor changes within the catchment areas and study the height changes towards the inland of Greenland. The penetration of X-band SAR shows significant influence on height measurements especially in these areas and must be considered for accurate ...